Unveiling the structure of the primary caseinate particle using small-angle X-ray scattering and simulation methodologies. (November 2021) - Sun, Yang; Tai, Zhonghong; Yan, Tingting; Dai, Yiqi; Hemar, Yacine; Li, Na
Graphical abstract: Structure of casein clusters obtained by a combination of SEC, AUC, electrophoresis, SAXS with MD simulations. Highlights: Unveiling the structure of the primary caseinate particle using SAXS and simulation methodologies. Molar mass, structural information and ab initio model for casein clusters were obtained. Casein clusters consisted of 64.3% of αs1 -β-αs2 -CN, 22.3% of αs1 -CN, 8.5% of αs2 -CN, and 4.4% of αs1 -αs2 -CN. αs1 -β-αs2 -CN species coexisted in ~35.3% of compact conformation and ~64.7% in elongated conformation. αs1 -β-αs2 -CN underwent an elongated to compact conformational change in the initial 200 ns MD simulations. Abstract: The low-resolution structure of casein (CN) clusters in sodium caseinate (NaCas) solution and its conformational dynamics were obtained by size-exclusion chromatography (SEC), analytical ultracentrifugation (AUC), small-angle X-ray scattering (SAXS), and molecular dynamics (MD) simulations. The results of sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS-PAGE) and native PAGE revealed that the casein clusters consisted predominantly of α- and β-CN complexes, and a trace amount of κ-CN. The AUC analysis indicated that the casein clusters were composed of 34.6% of casein monomers, 19.2%, 20.4%, and 25.8% of complexes with molar weight ( M w ) of ~50.3, ~70.6, and ~133 kDa, respectively. The volume fractions of components in casein clusters were quantified as 64.3% of αs1 -β-αs2 -CN, 22.3% of αs1 -CN, 8.5% of αs2 -CN, and 4.4% of αs1 -αs2 -CN, respectively. The ensemble optimization method ( EOM ) gave a fitting result where αs1 -β-αs2 -CN species coexisted in ~35.3% under compact conformation and ~64.7% in elongated conformation in solution. The three-dimensional structures of αs1 -β-αs2 -CN from EOM showed a good overlay on the casein clusters ab initio model obtained from DAMMIN and DAMMIX program. MD simulations revealed that αs1 -β-αs2 -CN underwent a conformational change from the elongated state into the compact state within the initial 200 ns of simulations. The addition of nonionic surfactants affected little the backbone-to-backbone interactions in the formation of the casein clusters. We propose that αs1 -CN, β-CN, αs2 -CN, and κ-CN associated in consecutive steps into casein clusters, and a trace of κ-CN may be located at the surface of the assemblies limiting the growth of casein aggregates.